Penguatan Pengelolaan Keuangan Dan Perencanaan Usaha Untuk Mendukung Keberlanjutan Bisnis Peternakan Ayam Kampung - Lily Karlina Nasution; M Dwi Arjuna; Laelisneni Laelisneni (JPM: Jurnal Pengabdian Masyarakat, 2026)
The community service partners in this program were small-scale free-range native chicken farmers in Sigara-gara Village, Langkat Regency, Indonesia, who managed their businesses independently using simple and unstructured financial record-keeping systems. The main challenges encountered by the partners included the absence of a clear separation between business and household finances, inconsistent transaction recording, and the lack of business planning to support informed decision-making. These conditions made it difficult for the farmers to accurately identify production costs, profit levels, cash flow, and future business development needs, resulting in less effective business management. Therefore, this community service program aimed to enhance the partners' capacity in preparing simple financial records and developing business plans to improve the efficiency, effectiveness, and sustainability of their native chicken farming enterprises. The program contributed practical mentoring, user-friendly bookkeeping templates, and simple business planning guidelines tailored to the farmers' operational conditions. The implementation employed a participatory approach consisting of observation, needs assessment, socialization, training, mentoring, and evaluation. The training focused on recording cash receipts and expenditures, classifying production costs, preparing simple income statements, and developing short-term business plans based on financial information. The evaluation results indicated a significant improvement in the partners' managerial competencies. Before the program, only 30% of participants regularly recorded business transactions; after the program, this figure increased to 85%. The proportion of participants capable of preparing simple financial statements increased from 25% to 82%, while the ability to develop business plans improved from 20% to 78%. In addition, 90% of the participants expressed positive feedback regarding the mentoring activities, stating that the training materials were easy to understand and could be directly applied to their daily farming operations. Overall, this community service program successfully strengthened the managerial capacity of the partner farmers, promoted more effective financial management practices, and served as an initial step toward improving the long-term sustainability of native chicken farming businesses.